Gender and the local-global nexus theory, research, and action - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Amsterdam ; Boston : Elsevier JAI, 2006)
The nine papers in this volume have a world in which the local/global connection is salient as background. Examining gender and its implications for feminist action within this setting, they fall into three overlapping categories. The first, theory, involves the theoretical consideration of gender across place and time. The second, research, reveals cultural differences in attitudes toward gender, and the third, action, concerns the feminist implications of gender as hierarchy. Disciplines represented include archaeology, cultural anthropology, sociology, and urban studies. Comparing, contrasting, and critiquing, authors based in Australia, Brazil, Italy, New Zealand, and the United States report research findings and personal experiences from their home countries as well as Canada, Mexico, Siberia, Slovakia, and a range of Asian nations. In every instance, gender dynamics are shown to be challenging and complex and new insights and directions for gender research, theory and action are revealed. It discusses theory, research and action tied to gender and geographic location. A variety of cultures are represented from diverse countries in the Americas, Asia and Europe. It provides new insights and directions for gender research.
Introduction: gender and the local-global nexus - theory, research, and action / Vasilikie Demos, Marcia Texler Segal -- Thinking of gender in a holistic sense: understandings of gender in Sulawesi, Indonesia / Sharyn Graham Davies -- Variations in masculinity from a cross-cultural perspective / Edwin S. Segal -- Is there a need to (un)gender the past? / Denise Pahl Schaan -- Young people's attitudes to gender issues: Asian perspectives / Chilla Bulbeck -- A comparative analysis of sex role ideology in Canada, Mexico and the United States / Richard J. Harris, Juanita M. Firestone, Paul J. Bryan -- The "free university of women:" reflections on the conditions for a feminist politics of knowledge / Paola Melchiori -- Spy or feminist: "grrrila" research on the margin / Elizabeth L. Sweet -- Marketing social change after communism: the case of domestic violence in Slovakia / Magdalena Vanya -- life history as narrative subversion: older Mexican women resist authority, assert identity, and claim power / Tracy B. Citeroni.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sex role; Sex discrimination; Globalization -- Social aspects; Gender studies, gender groups; Social Science -- Gender Studies